STRATEGI DAN DESAIN PEMBELAJARAN PENDIDIKAN AGAMA HINDU BERBASIS KEARIFAN LOKAL - Dewa Kadek Sudyana; I Ketut Winantra (UNHI PRESS, 2021)
The learning process of Hinduism based on local culture and wisdom needs to be conveyed in the learning process as an effort to encourage students to study the Hindu Religious Education curriculum and increase students' insight and experience in accordance with the region and religious practices where they live through the integration of wisdom values. local. Hindu religious education in schools is a process of inculcating and teaching Hindu religious material and values ​​for Hindu students who are responsive to the local advantages of the area where they live, and have a self-identity that is based on the identity of the nation and state in facing national and international competition. global and build religious moderation. However, at this time the teaching of Hindu religious education presented by the Ministry of Education and Culture has not opened up space for local wisdom that is regional in nature. This is what causes Hindu religious education teachers to try to be able to make strategies and designs in Hindu religious education based on local wisdom. The method used to solve the problem is a qualitative method where the data collection and data presentation is done descriptively. The types and sources of data are primary and secondary data. Data collection is carried out using structured and in-depth interviews with purposive determination of respondents, observations are carried out continuously, and data analysis is carried out using triangulation techniques. The results of this study are the relationship between Hinduism and local wisdom, learning strategies for Hindu Religious Education based on local wisdom, learning design for Hindu religious education based on local wisdom, and obstacles in designing learning for Hindu Religious Education based on local wisdom.